2017
DOI: 10.1515/ijfe-2016-0344
|View full text |Cite
|
Sign up to set email alerts
|

Colour, Texture, Microstructure and Nutrient Retention of Kiwifruit Slices Subjected to Combined Air-Impingement Jet Drying and Freeze Drying

Abstract: The aim of this study was to select an appropriate drying technique from air-impingement jet drying (AIJD), hot air drying (HAD) and microwave drying (MWD) which can be combined with freeze drying (FD). Results showed that AIJD with relatively high efficiency, low energy consumption and good drying quality was suitable to be combined with FD. To further improve the drying technology of kiwifruits, the energy consumption and quality of dried kiwifruit with different conversion point during combined FD and AIJD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 33 publications
4
11
0
2
Order By: Relevance
“…(2014) also found a similar result in American ginseng during AIJD processing. In this study, the drying dynamics of B. aereus slices were affected by drying temperature, which is similar to the results of AIJD in kiwifruit slices (Huang et al., 2017) and onion (Li et al., 2015). Figures 1(a) and 1(c) showed that the water diffusion rate of B. aereus slices accelerated with the increasing of drying temperature, which resulted in a shorter time spent in drying.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…(2014) also found a similar result in American ginseng during AIJD processing. In this study, the drying dynamics of B. aereus slices were affected by drying temperature, which is similar to the results of AIJD in kiwifruit slices (Huang et al., 2017) and onion (Li et al., 2015). Figures 1(a) and 1(c) showed that the water diffusion rate of B. aereus slices accelerated with the increasing of drying temperature, which resulted in a shorter time spent in drying.…”
Section: Resultssupporting
confidence: 88%
“…Xiao et al (2014) also found a similar result in American ginseng during AIJD processing. In this study, the drying dynamics of B. aereus slices were affected by drying temperature, which is similar to the results of AIJD in kiwifruit slices (Huang et al, 2017) and onion (Li et al, 2015). Figures 1(a (Li et al, 2013).…”
Section: Drying Curves Of B Aereus Slicessupporting
confidence: 88%
See 1 more Smart Citation
“…Kiwifruit has been investigated for convective drying by several researchers ( 21 , 27 30 ). Similarly, changes in colour ( 25 , 31 , 32 ) and physical properties ( 33 , 34 ) of hot air convective dried kiwifruit have been published. The influence of conventional drying conditions on bioactive compounds in fresh and dried kiwifruit has also been examined by Tian et al ( 22 ), Orikasa et al ( 23 ) and Kaya et al ( 24 ).…”
mentioning
confidence: 99%
“…(2016) sıcak haddelemede en önemli işlemlerden biri olan ve herhangi bir sanayi sürecinde en fazla su tüketimlerinden birine sahip olan soğutma sürecinin taşınım ısı transferi olgusunu anlamak için kaynama noktasının altındaki sıcaklıklarda sıcak bir düz çelik plaka üzerine türbülanslı su jeti çarpmasıyla ısı transferinin sayısal araştırmasını yapmışlardır. (11) Yukarıdaki denklemler aşağıdaki giriş ve sınır şartlarının kullanılmasıyla FLUENT programında kullanıcı tanımlı bir fonksiyon kodu (UDF) yazılarak çözülmüştür.…”
Section: Gġrġġunclassified